Evaluation of some Physicochemical Characteristics of Soil from Namtari, Yola South, Adamawa State, Nigeria - A. Garba; M. A. Qadeer; I. Kabiru (Journal of Applied Sciences and Environmental Management)
The objective of this paper is to evaluate some physicochemical characteristics of soil from Namtari Ward, Yola South LGA, Adamawa State, Nigeria using appropriate standard procedures. Data obtained shows that: Soil pH ranged from slightly acidic (7.04 ± 0.35) to slightly alkaline (7.37 ± 0.55), while organic matter content varied from 2.53 ± 0.28% (Karlahe) to 6.17 ± 0.67% (Changala). Nitrogen levels ranged from 0.126 ± 0.01 gkg⁻¹ (Dadi) to 0.316 ± 0.02 gkg⁻¹ (Changala), and phosphorus levels from 15.03 ± 1.5 gkg⁻¹ (Karlahe) to 18.91 ± 1.116 gkg⁻¹ (Dadi). Potassium levels spanned 0.73 ± 0.07 cmolkg⁻¹ (Dadi) to 1.956 ± 0.69 cmolkg⁻¹ (Changala), and moisture content was highest in Karlahe (61.16 ± 3.403%) and lowest in Changala (48.16 ± 7.42%). The results indicate significant changes in soil parameters, particularly a reduction in organic matter and moisture content, and slight changes in pH due to climate factors. These findings suggest that climate change contributes to soil degradation, with potential implications for agricultural productivity and ecosystem health. Practices like crop diversification, conservation tillage, and agroforestry were recommended to lessen the impact of climate variability on soil health and crop productivity. Providing farmers with training and resources will aid their shift toward these sustainable methods.